2003
DOI: 10.1074/jbc.m301361200
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi Protein RCAS1 Controls Cell Surface Expression of Tumor-associated O-Linked Glycan Antigens

Abstract: Tumor immunology has received a large impetus from the identification of tumor-associated antigens. Among them, a monoclonal antibody, 22.1.1, was instrumental in defining a novel tumor-associated antigen that was termed "receptor binding cancer antigen expressed on SiSo cells" (RCAS1). RCAS1 was proposed to induce growth arrest and apoptosis on activated immune cells, mediated by a putative death receptor. Structurally, RCAS1 was predicted to exist as a type II transmembrane protein and in a soluble form. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 37 publications
5
69
0
Order By: Relevance
“…These data indicate that at least a fraction of exosomal GPRC5B proteins originated from the cell surface. Using the same labeling protocol combined with subcellular fractionation in a sucrose gradient, biotinylated GPRC5B-HA protein was recovered from intracellular fractions that also contained RCAS1 (also known as EBAG9), a Golgi-resident protein (43), at 30 min after cell surface labeling (Fig. 4B), demonstrating that GPRC5B proteins are internalized from the cell surface, which likely occurs prior to their release into exosomes.…”
Section: A Fraction Of Gprc5b Proteins Is Internalized From the Cell mentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that at least a fraction of exosomal GPRC5B proteins originated from the cell surface. Using the same labeling protocol combined with subcellular fractionation in a sucrose gradient, biotinylated GPRC5B-HA protein was recovered from intracellular fractions that also contained RCAS1 (also known as EBAG9), a Golgi-resident protein (43), at 30 min after cell surface labeling (Fig. 4B), demonstrating that GPRC5B proteins are internalized from the cell surface, which likely occurs prior to their release into exosomes.…”
Section: A Fraction Of Gprc5b Proteins Is Internalized From the Cell mentioning
confidence: 99%
“…Given the perinuclear distribution of GPRC5B-HA as well as the co-fractionation of GPRC5B-HA with the Golgi marker RCAS1 (43) (Fig. 4B), we asked whether this structure corresponds to the Golgi complex.…”
Section: A Fraction Of Gprc5b Proteins Is Internalized From the Cell mentioning
confidence: 99%
“…The supranuclear positivity could indicate the presence of Golgi apparatus (Ross et al, 1989), because PNA binds many O-linked oligosaccharides containing GalNAc (Spicer and Schulte, 1992) and O-linked glycans are synthesized in the Golgi complex (Engelsberg et al, 2003). The epithelium lining the crypts of the distal colon showed a more complex glycoconjugate pattern than in the cecum.…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated whether EBAG9 overexpression could alter cell surface glycosylation as previously reported (9), using another mAb clone, 22.1.1, which detects the tumor-associated Tn antigen (22.1.1 antigen) induced on the cell surface (9). As shown in Fig.…”
Section: Cellular Localization Of Full-length and Truncated Ebag9mentioning
confidence: 99%
“…Nakashima et al (6) demonstrated that EBAG9 was a type II membrane protein that had a C-terminal coiled-coil region at the cell surface that could bind to the putative receptor in T cells and NK cells, thereby inducing their apoptotic cell death (6), and named it receptor-binding cancer antigen expressed on SiSo cells (RCAS1). However, Engelsberg et al presented a new finding that EBAG9 was a Golgi-resident protein that modulates cell surface glycosylation by a series of biochemical and cellular imaging analyses (7)(8)(9)(10)(11). They proposed that EBAG9-overexpression might contribute to the antigenicity of tumor cells by generation of the tumor-associated O-linked glycan Tn antigen (for example, 22.1.1 antigen).…”
Section: Introductionmentioning
confidence: 99%